Development of Entrepreneurial Teaching Materials by Using Project-Based Learning Model in Improving Students' Creativity and Self-Confidence - Iswidana Utama Putra; Nopriansah Nopriansah; Melly Susanti (Jurusan Manajemen Pendidikan Islam Fakultas Tarbiyah dan Keguruan UIN Sultan Maulana Hasanuddin Banten, 2020)
This development research aimed to produce entrepreneurship teaching materials by using the PjBL method and improving student learning outcomes in running a small handicraft business. The research that was carried out is a development research (research and development) and followed by a quasi experiment (quasi experiment) that collaborates with class teachers. The research stages to be carried out are: (1) the preparation stage, (2) the development stage, (3) the experimental stage, (4) evaluation. At the stage of developing teaching materials using the Plomp model (2010) which includes (1) preliminary research, (2) prototyping phase, and (3) assessment phase. Furthermore, at the application stage a collaborative experiment is carried out in which the learning is carried out in collaboration with the teacher. The subjects of this study were teachers and students from SMA/MA/SMKN in North Bengkulu. In the experimental stage, it was carried out by taking two classes from each school as the experimental class and the control class. The target achievement in this study is the creation of entrepreneurship teaching materials that meet valid and practical criteria and there is an effect of project-based learning teaching materials on students' abilities and self-confidence.